Gas sensor based on zinc vanadate nano material

By using the sol-gel method to synthesize ZnVO4 nanomaterials as the sensitive layer of the gas-sensitive sensor, the problems of insufficient sensitivity and long response time of existing sensors are solved, and high sensitivity detection and rapid response to SOF2 gas are achieved, and high-temperature and high-humidity environments are adapted to high-temperature and high-humidity environments are adapted.

CN119534558APending Publication Date: 2025-02-28GUANGXI POWER GRID CO LTD NANNING POWER SUPPLY BUREAU
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411472992.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing gas-sensitive sensors for SF6 decomposition product SOF2 are insufficient in sensitivity and have a long response time, making it difficult to meet actual monitoring needs, especially in high temperature and high humidity environments, which greatly reduce performance.

Method used

ZnVO4 nanomaterial was synthesized by sol-gel method as the sensitive layer material of the gas-sensitive sensor, and interdigital electrodes were prepared by MEMS process, and the ZnVO4 nanomaterial was uniformly coated on the electrode using a spin coating process to form a dense gas-sensitive layer.

Benefits of technology

It realizes high sensitivity detection of SOF2 gas, shortens the response time to 5 minutes, has good linear response characteristics and environmental adaptability, and can work stably in high temperature and high humidity environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534558A_ABST
    Figure CN119534558A_ABST
Patent Text Reader

Abstract

The invention discloses a gas sensor based on a zinc vanadate nano material, and relates to the technical field of preparation of gas sensors. The gas sensor comprises a substrate, an interdigital electrode and a sensitive layer material coated on the interdigital electrode, and the sensitive layer material is a ZnVO4 nano material. The zinc vanadate nano material is used as a sensitive layer material of the gas sensitive sensor, so that the gas sensitive sensor shows good gas sensing performance on a decomposition product SOF2 gas of SF6, and has the advantages of high sensitivity, high response and recovery speed and high environmental adaptability. In practical application, the gas-sensitive sensor can realize sensitive detection at a low SOF2 concentration, the response time is shortened to 5 min, the gas-sensitive sensor has good linear response characteristics, the sensor shows stable gas-sensitive performance after multiple cycle tests, and meanwhile, the sensor is made of a high-temperature-resistant and moisture-resistant material, can adapt to a high-temperature and high-humidity environment, and has wide application prospects. Good application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas sensor preparation, and in particular to a gas sensor based on zinc vanadate nanomaterials. Background Art

[0002] Sulfur hexafluoride (SF6) is an insulating gas commonly used in high-voltage electrical equipment. It is widely used due to its excellent insulation performance and arc extinguishing ability. However, during the long-term operation of the equipment, SF6 may decompose due to arc discharge, local overheating, etc., generating some chemically active byproducts, such as thionyl fluoride (SOF2). The accumulation of these decomposition products will reduce the insulation performance of the equipment and even threaten the stability and safety of the system. Therefore, online detection and monitoring of these decomposition products is crucial to ensure the reliable operation of the power system.

[0003] In the prior art, the gas sensors for SF6 decomposition products such as SOF2 are not sensitive enough and have a long response time, which makes it difficult to meet the actual monitoring needs. Especially in complex environments such as high temperature and high humidity, the gas-sensing performance of existing materials is greatly reduced. Patent CN 114132961 A, a method for preparing spherical zinc vanadate, discloses that spherical zinc vanadate has potential application value in gas sensors. However, since different gas sensors have different sensitivities and selectivities for different gases, it is not clear whether the spherical zinc vanadate prepared by this method can be used in gas sensors to detect SF6 decomposition products such as SOF2, and it is even more unclear whether it can quickly detect SF6 decomposition products in high temperature and high humidity environments. Therefore, the development of a sensor material with high sensitivity, fast response, and adaptability to complex environments has become a technical problem that needs to be solved urgently.

[0004] In summary, the present invention provides a gas sensor based on zinc vanadate nanomaterials for online detection and monitoring of SOF2, a decomposition product of insulating gas SF6 in high-voltage electrical equipment. Summary of the invention

[0005] In view of the above shortcomings, the present invention provides a gas sensor based on zinc vanadate nanomaterials, which solves the problem of insufficient sensitivity and long response time of existing gas sensors for SF6 decomposition products such as SOF2. The specific technical solution is as follows:

[0006] A gas sensor based on zinc vanadate nanomaterials, comprising a substrate, interdigital electrodes, and a sensitive layer material coated on the interdigital electrodes, wherein the sensitive layer material is a ZnVO4 nanomaterial.

[0007] Furthermore, the ZnVO4 nanomaterial is synthesized by a sol-gel method, which specifically includes: first dissolving zinc nitrate and sodium vanadate in distilled water respectively, then mixing and stirring the two solutions evenly, adding an appropriate amount of citric acid and stirring to react to obtain a sol, then drying the obtained sol into a gel, and calcining the gel to obtain the ZnVO4 nanomaterial.

[0008] Furthermore, the molar concentration of the zinc nitrate and sodium vanadate is 0.1-0.3M.

[0009] Furthermore, the mixture is zinc nitrate and sodium vanadate mixed in a molar ratio of 1:1-3. The applicant has found through a large number of experiments that exceeding the above ratio range will seriously affect the morphology and performance of the ZnVO4 nanomaterial.

[0010] Furthermore, the amount of citric acid added is 1-1.5 times the molar number of the sodium vanadate. Adding citric acid and controlling the amount within this range can control the size of the ZnVO4 nanoparticles and make the size and morphology of the ZnVO4 nanoparticles uniform.

[0011] Furthermore, the stirring reaction temperature is 50-65° C., and the stirring time is 1-2 h.

[0012] Furthermore, the drying temperature of the sol is 100-180°C; the calcination temperature of the gel is 450-550°C, and the calcination time is 2-3h. This temperature can ensure that the ZnVO4 nanoparticles are not destroyed.

[0013] The preparation method of the gas sensor based on zinc vanadate nanomaterial of the present invention comprises the following steps:

[0014] (1) Cleaning and drying the alumina ceramic substrate;

[0015] (2) preparing interdigital electrodes on the substrate by MEMS process, wherein the electrodes are made of gold thin films and deposited on the substrate by electron beam evaporation process;

[0016] (3) The ZnVO4 nanomaterial is dispersed in an ethanol solution, and the ethanol solution containing the ZnVO4 nanomaterial is evenly coated on the interdigital electrodes by a spin coating process, and then dried and sintered at a high temperature to form a dense gas-sensitive layer, thereby obtaining the gas sensor.

[0017] The present invention also provides a use of the above-mentioned gas sensor, which is mainly used for online detection and monitoring of SOF2, a decomposition product of insulating gas SF6 in high-voltage electrical equipment.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The present invention uses zinc vanadate nanomaterials as the sensitive layer material of the gas sensor, so that the gas sensor exhibits good gas sensing performance for SOF2 gas, a decomposition product of SF6, and has the advantages of high sensitivity, fast response and recovery speed, and strong environmental adaptability. In practical applications, the gas sensor of the present invention can achieve sensitive detection at a relatively low SOF2 concentration, the detection limit can reach 10ppm, the response time is shortened to 5min, and has good linear response characteristics; after multiple cycle tests, the sensor exhibits stable gas-sensitive performance; at the same time, the sensor of the present invention uses high temperature resistant and moisture-resistant materials, and can adapt to high temperature and high humidity environments. Therefore, the gas sensor of the present invention is expected to be used for the detection and monitoring of SOF2, a decomposition product of the insulating gas SF6 in high-voltage electrical equipment.

[0020] 2. The preparation method of the present invention can be used to prepare a ZnVO4 nanomaterial with a unique crystal structure and excellent gas adsorption capacity. The ZnVO4 nanomaterial is a layered sheet structure with a very high specific surface area and abundant surface active sites. The crystal structure effectively improves the gas-sensitive performance of the sensor, enabling it to respond significantly to SOF2 gas at room temperature and have a rapid recovery ability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.

[0022] Figure 1 This is a transmission electron microscope image of the ZnVO4 nanoparticles in Example 1 of the present invention.

[0023] Figure 2 This is the response curve of the gas sensor in Example 1 of the present invention to the SOF2 gas concentration.

[0024] Figure 3 It is the response characteristic curve of the gas sensor in Example 2 of the present invention to different gases. DETAILED DESCRIPTION

[0025] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0026] Example 1

[0027] The method for preparing a gas sensor based on zinc vanadate nanomaterials in this embodiment comprises the following steps:

[0028] (1) Substrate preparation

[0029] An alumina ceramic substrate was used, and after ultrasonic cleaning, it was cleaned in acetone, isopropanol and deionized water for 5 minutes respectively to ensure that there was no contaminant on the surface of the substrate, and then dried at 80°C for 30 minutes.

[0030] (2) Electrode preparation

[0031] The interdigital electrodes were prepared on an alumina substrate using a micro-electromechanical system (MEMS) process. A 100 nm thick gold (Au) film was deposited on the substrate using electron beam evaporation technology, and the electrode pattern formed on the gold film was defined by a photolithography process, with the spacing of the interdigital electrodes set to 20 μm.

[0032] (3) Preparation of zinc vanadate nanomaterials

[0033] ZnVO4 nanoparticles were prepared by sol-gel method. First, 0.1M zinc nitrate (Zn(NO3)2) and 0.1M sodium vanadate (Na3VO4) were dissolved in distilled water respectively, and then zinc nitrate and sodium vanadate were mixed in a molar ratio of 1:1, stirred evenly, and then an appropriate amount of citric acid was added as a complexing agent, and the amount of citric acid added was 1.5 times the molar number of the sodium vanadate. The solution was stirred and reacted at 60°C for 2 hours, and then the obtained sol was dried at 150°C, and the dried gel was calcined at 500°C for 3 hours to form ZnVO4 nanoparticles. The crystal structure of the zinc vanadate nanomaterial prepared in this embodiment is as shown Figure 1 As shown, its crystal structure is a stacked lamellar structure with a high specific surface area and abundant surface active sites. This crystal structure effectively improves the gas-sensitive performance of the sensor, enabling it to respond significantly to SOF2 gas at room temperature and have rapid recovery capabilities.

[0034] (4) Gas-sensitive material coating

[0035] The prepared ZnVO4 nanoparticles were dispersed in an ethanol solution and dispersed by ultrasonic for 10 minutes to make the particles evenly distributed. The nanoparticle solution was evenly coated on the surface of the interdigital electrode by spin coating. After coating, the sensor was placed at 80°C to dry to obtain a gas sensor.

[0036] (5) Sensor packaging

[0037] After the sensor is prepared, it is packaged with UV glue to ensure the stability of the device in complex environments such as high temperature and high humidity. The final packaged sensor is connected to the data acquisition system for gas testing and performance evaluation.

[0038] Example 2

[0039] The method for preparing a gas sensor based on zinc vanadate nanomaterials in this embodiment comprises the following steps:

[0040] (1) Substrate preparation

[0041] An alumina ceramic substrate was used, and after ultrasonic cleaning, it was cleaned in acetone, isopropanol and deionized water for 5 minutes respectively to ensure that there was no contaminant on the surface of the substrate, and then dried at 80°C for 30 minutes.

[0042] (2) Electrode preparation

[0043] The interdigital electrodes were prepared on an alumina substrate using a micro-electromechanical system (MEMS) process. A 100 nm thick gold (Au) film was deposited on the substrate using electron beam evaporation technology, and the electrode pattern formed on the gold film was defined by a photolithography process, with the spacing of the interdigital electrodes set to 20 μm.

[0044] (3) Preparation of zinc vanadate nanomaterials

[0045] ZnVO4 nanoparticles were prepared by sol-gel method. First, 0.3M zinc nitrate (Zn(NO3)2) and 0.3M sodium vanadate (Na3VO4) were dissolved in distilled water, respectively, and then zinc nitrate and sodium vanadate were mixed in a molar ratio of 1:2, and after stirring, an appropriate amount of citric acid was added as a complexing agent, and the amount of citric acid added was 1 times the molar number of the sodium vanadate. The solution was stirred at 50°C for 2 hours, and then the obtained sol was dried at 180°C, and the dried gel was calcined at 450°C for 2 hours to form ZnVO4 nanoparticles. The crystal structure of the zinc vanadate nanomaterial obtained in this embodiment is a laminated sheet structure with a high specific surface area and abundant surface active sites. The crystal structure effectively improves the gas-sensitive performance of the sensor, so that it can produce a significant response to SOF2 gas at room temperature, and has a rapid recovery ability.

[0046] (4) Gas-sensitive material coating

[0047] The prepared ZnVO4 nanoparticles were dispersed in an ethanol solution and dispersed by ultrasonic for 10 minutes to make the particles evenly distributed. The nanoparticle solution was evenly coated on the surface of the interdigital electrode by spin coating. After coating, the sensor was placed at 80°C to dry to obtain a gas sensor.

[0048] (5) Sensor packaging

[0049] After the sensor is prepared, it is packaged with UV glue to ensure the stability of the device in complex environments such as high temperature and high humidity. The final packaged sensor is connected to the data acquisition system for gas testing and performance evaluation.

[0050] Test Example 1: SOF2 gas sensitivity test

[0051] Test Example 1 The response of zinc vanadate (ZnVO4) gas sensor to different concentrations of SOF2 gas was obtained. The experimental device includes a gas generator, a sensor test box and a data acquisition system. SOF2 gas is injected into the test box through a mixed gas generator, and the gas concentration is adjusted to 20ppm, 30ppm, 50ppm, 80ppm and 100ppm respectively. The sensor is tested at room temperature. The test results are shown in Figure 2 , Figure 2 This is the response curve of the gas sensor to the SOF2 gas concentration. The graph shows that with the increase of SOF2 gas concentration, the response value of the sensor gradually increases, and it has the ability to detect trace amounts of SOF2 gas.

[0052] Test Example 2: Experiment on the selectivity of different gases to the sensor

[0053] Test Example 2 The response of zinc vanadate (ZnVO4) gas sensor to different gases was tested. In addition to SOF2, the tested gases also included other common gases such as SO2, NO2, CO2 and H2S, all with a concentration of 50ppm. The gases were injected into the sensor test system one by one, and the response signals of the sensors were recorded. The results are shown in Figure 3 , Figure 3 It is the response characteristic curve of the gas sensor to different gases. The figure shows that the sensor responds most obviously to SOF2 gas, while the response to other gases is weaker, indicating that the sensor has good selectivity to SOF2.

[0054] In summary, the present invention uses zinc vanadate nanomaterials as the sensitive layer material of the gas sensor, so that the gas sensor exhibits good gas sensing performance for SOF2 gas, a decomposition product of SF6, and has the advantages of high sensitivity, fast response and recovery speed, and strong environmental adaptability. In practical applications, the gas sensor of the present invention can achieve sensitive detection at a lower SOF2 concentration, the response time is shortened to 5min, and has good linear response characteristics; after multiple cycle tests, the sensor exhibits stable gas-sensitive performance; at the same time, the sensor of the present invention uses high temperature resistant and moisture-resistant materials, and can adapt to high temperature and high humidity environments. Therefore, the gas sensor of the present invention is expected to be used for the detection and monitoring of SOF2, a decomposition product of insulating gas SF6 in high-voltage electrical equipment. In addition, the preparation method of the present invention can be used to obtain a ZnVO4 nanomaterial with a unique crystal structure and excellent gas adsorption capacity. The ZnVO4 nanomaterial is a stacked sheet structure with a high specific surface area and abundant surface active sites. The crystal structure effectively improves the gas-sensitive performance of the sensor, so that it can produce a significant response to SOF2 gas at room temperature and has a rapid recovery ability.

[0055] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A gas sensor based on zinc vanadate nanomaterials, the gas sensor comprising a substrate, interdigital electrodes, and a sensitive layer material coated on the interdigital electrodes, characterized in that: The sensitive layer material is ZnVO4 nanomaterial.

2. A gas sensor based on zinc vanadate nanomaterial according to claim 1, characterized in that: The ZnVO4 nanomaterial is synthesized by a sol-gel method, specifically comprising: first dissolving zinc nitrate and sodium vanadate in distilled water respectively, then mixing and stirring the two solutions evenly, adding an appropriate amount of citric acid and stirring to react to obtain a sol, then drying the obtained sol into a gel, and calcining the gel to obtain the ZnVO4 nanomaterial.

3. A gas sensor based on zinc vanadate nanomaterial according to claim 2, characterized in that: The molar concentration of the zinc nitrate and sodium vanadate is 0.1-0.3M.

4. A gas sensor based on zinc vanadate nanomaterial according to claim 2, characterized in that: The mixing is zinc nitrate and sodium vanadate mixed in a molar ratio of 1:1-3.

5. A gas sensor based on zinc vanadate nanomaterial according to claim 2, characterized in that: The amount of citric acid added is 1-1.5 times the molar number of the sodium vanadate.

6. A gas sensor based on zinc vanadate nanomaterial according to claim 2, characterized in that: The stirring reaction temperature is 50-65°C and the stirring time is 1-2h.

7. A gas sensor based on zinc vanadate nanomaterial according to claim 2, characterized in that: The drying temperature of the sol is 100-180° C.; the calcination temperature of the gel is 450-550° C., and the calcination time is 2-3 hours.

8. Use of the gas sensor according to any one of claims 1 to 7, characterized in that: The gas sensor is used for online detection and monitoring of the decomposition product SOF2 of the insulating gas SF6 in high-voltage electrical equipment.

Citation Information

Patent Citations

  • Preparation method of spherical zinc vanadate

    CN114132961A